Desenvolvimento e caracterização de leitor portátil por luminescência opticamente estimulada - Lazzari, Rodrigo de (2024)
The OSL technique for dosimetry of ionizing radiation has been consolidated in the last decade. In this technique, the dosimetric material, after being exposed to ionizing radiation, is subjected to an external optical stimulus that leads to OSL emission. The OSL reader is equipment that allows quantifying the dose of ionizing radiation to which the sample was previously exposed, stimulating it with light at certain wavelengths, and detecting the signal emitted. Considering the growth and consolidations of the OSL technique, as well as the lack of instrumentation, mainly in the national market, this work was built and characterized an OSL reader called RAD – Radiation Dosimetry system. With a relatively low cost, compared to readers available for import, opensource software and a bold layout were used, offering great innovations in variations of options for optical stimulation (different wavelengths) and carrying out readings of different samples of materials with different stimulus modes (continuous or pulsed). Each RAD module was evaluated through stimulation LED stability, detector module stability and sensitivity tests. The characterization tests were carried out using Al2O3:C (Luxel – Landauer Inc.) and CaF2 (OSL – UTFPR films) detectors. For intercomparison, measurements were also taken of the same detectors in commercial readers, making it possible to compare the sensitivity of the RAD in relation to other equipment, the RAD reader has relatively lower sensitivity. This characteristic is related to the sources of optical stimulation. In POSL mode, the sensitivity was compared with a commercial Microstar reader (Landauer Inc), while in CW-OSL mode, the measured sensitivity was compared with the Risø reader, TL/OSL – DA20 (DTU – Nutech. In the detectors used in the tests, the lowest dose evaluated with the RAD was tens of mGy, reaching hundreds of Gy. Although in continuous mode the sensitivity is relatively lower, the cost-benefit and the advantage of reading any type and size of sample makes RAD reader notable for its use. Additionally, an increase in sensitivity can be trained by increasing the power of the stimulation source. To demonstrate the applicability of the RAD reader, the lifetime of the Al2O3:C and CaF2 detectors are measured, being compatible with the values presented in the literature (approximately 35 ms). The prototype developed is one of the few models currently existing in Brazil, already in use at LabLED (Stimulated Luminescence and Dosimetry Laboratory) from UTFPRCT.